2000
DOI: 10.1902/jop.2000.71.10.1561
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Non‐Surgical Therapy on Gingival Inflammatory Cell Subsets in Patients With Adult and Early‐Onset Periodontitis

Abstract: Local cellular immunity in patients with adult onset periodontitis does not appear to differ from the immune response in patients with early onset periodontitis. Scaling and root planing causes a decrease in the inflammatory cells subsets tested, however, this decline seems to be more pronounced in EOP than in AP subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…With respect to T lymphocyte density in chronic gingivitis, the present results do not agree with the literature, as most studies implicate T lymphocyte as the main cell type found in the inflammatory infiltrate during the initial stages of gingivitis (8,9). A labeling intensity score of 1 for CD4+ cells was exclusively observed in CP specimens, corroborating the studies of Kleinfelder et al (10). The fact that this experiment was restricted to the investigation of CD4+ T lymphocytes also seems to explain the reduced density of positive T cells observed in this sample because, even in small numbers, CD8+ T lymphocytes are also present in CP, as reported by Séguier et al (11).…”
Section: Discussioncontrasting
confidence: 77%
“…With respect to T lymphocyte density in chronic gingivitis, the present results do not agree with the literature, as most studies implicate T lymphocyte as the main cell type found in the inflammatory infiltrate during the initial stages of gingivitis (8,9). A labeling intensity score of 1 for CD4+ cells was exclusively observed in CP specimens, corroborating the studies of Kleinfelder et al (10). The fact that this experiment was restricted to the investigation of CD4+ T lymphocytes also seems to explain the reduced density of positive T cells observed in this sample because, even in small numbers, CD8+ T lymphocytes are also present in CP, as reported by Séguier et al (11).…”
Section: Discussioncontrasting
confidence: 77%
“…This clinical procedure might have contributed to decreased gingival inflammation and hence to an underestimation of APRIL and BLyS expression, although this is not certain. In this regard, it has been reported that scaling and root planing does not significantly affect the inflammatory infiltrate (B cells, plasma cells, and memory T cells) associated with chronic periodontitis (51). …”
Section: Discussionmentioning
confidence: 99%
“…Successful periodontal therapy results clinically in shallow PDs and a low tendency towards BOP and microbiologically, in a low detection level of periodontal pathogens (Haffajee et al 1997). In addition, it reduces the size of the inflamed lesion and causes a decrease in the periodontal tissues of inflammatory cell subsets, like B cells, T cells and plasma cells (Jully et al 1986, Berglundh et al 1999, Kleinfelder et al 2000). As in the present study, these clinical and microbiological outcomes of the therapy have been accomplished, it may be suggested that the number of inflammatory cells in the lesions also decreased.…”
Section: Discussionmentioning
confidence: 99%